2009
DOI: 10.1126/science.1172815
|View full text |Cite
|
Sign up to set email alerts
|

IL-21R on T Cells Is Critical for Sustained Functionality and Control of Chronic Viral Infection

Abstract: Chronic viral infection is often associated with the dysfunction of virus-specific T cells. Our studies using Il21r-deficient (Il21r-/-) mice now suggest that interleukin-21 (IL-21) is critical for the long-term maintenance and functionality of CD8+ T cells and the control of chronic lymphocytic choriomeningitis virus infection in mice. Cell-autonomous IL-21 receptor (IL-21R)-dependent signaling by CD8+ T cells was required for sustained cell proliferation and cytokine production during chronic infection. Il21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
397
1
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 401 publications
(420 citation statements)
references
References 21 publications
20
397
1
2
Order By: Relevance
“…Moreover, the data also indicate that IL-13-and IL-21-secreting HIV-specific T cells before ATI are associated with a lower viral replication following ATI, an immunological feature described in elite controllers [14,15]. As observed following therapeutic immunization of patients or in models of SIV pathogenesis, the ability to produce IL-2 CD4 + T cells appears to be critical for the maintenance of the proliferative capacity of CD8 + T cells [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the data also indicate that IL-13-and IL-21-secreting HIV-specific T cells before ATI are associated with a lower viral replication following ATI, an immunological feature described in elite controllers [14,15]. As observed following therapeutic immunization of patients or in models of SIV pathogenesis, the ability to produce IL-2 CD4 + T cells appears to be critical for the maintenance of the proliferative capacity of CD8 + T cells [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Schmitt et al (43) showed that IL-12 from PRR-stimulated DCs directly acts on memory CD4 + T cells to promote the secretion of IL-21. It is plausible that differences in the abundance of IL-21-dependent signals produced by CD4 + T cells are involved in the increased exhaustion of polyfunctional CD8 + T cells (37,38) in CP-Ds relative to CP-Ns; this awaits formal examination.…”
Section: Discussionmentioning
confidence: 99%
“…1, Supplemental Table 1). Although the requirement for CD4 + T cell help throughout chronic infection to sustain CD8 + T cell function (37,38) is not in dispute, PRRactivated DCs could represent a backup mechanism for situations in which CD4 responses are defective. This would be in keeping with findings by other investigators in which the adoptive transfer of autologous DCs loaded in vitro with whole-inactivated HIV-1 or therapeutic vaccination with a recombinant viral vector, both of which recruit functional DCs into the APC pool, induces protective antiviral immunity and viral suppression in the setting of chronic HIV-1 infection (39) and synergizes with PD-L1 neutralization to clear infection in CD4 + T cell help-deficient LCMV clone 13-infected mice (40), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Cependant, les éléments régulateurs clés produits par les cellules T CD4 + et nécessaires à l'obtention d'une réponse antivirale complète et efficace étaient jusqu'à récemment, mal compris, voire inconnus. Trois études récentes réalisées sur des mo dèles in vivo murins d'infection virale persistante par le lymphocytic choriomeningitis virus (LCMV) ont démontré le rôle clé de l'IL-21 dans la réponse antivirale [14][15][16]. Lors de ces études, les auteurs ont utilisé deux souches différentes de LCMV (clone 13 et Armstrong) qui possèdent une pathogénicité différente chez l'animal inoculé.…”
Section: L'interleukine-21unclassified